Levels of hormones and minerals in cyclic, anestrus and subestrus buffalo heifers - Sharma, K B; Nayyar, Shashi; Malik, V S; Singh, Rajvir; Sodhi, S P S (The Indian Journal of Animal Sciences, 2012)
The levels of hormones and minerals were studied in 40 normal cyclic, anestrus and subestrus buffalo heifers. The anestrus animals had lower hormonal and mineral (estradiol, thyroid hormones, inorganic phosphorus, iron and copper) concentrations. A specific balance of hormones/minerals is essential for the normal reproductive performance of buffaloes.